Viscoelastic simulations in polymer processing. - Barakos, George. (University of Ottawa (Canada), 1994)
The scope of this thesis is the mathematical modelling and the numerical simulation of polymer processing. In recent years there has been considerable progress in understanding and modelling phenomena related to flow of polymer melts through polymer processing machinery. Much of the progress is due to the numerical solution of integral-type constitutive equations relating stress and deformation and representing the fading memory of these fluids. In this direction, an integral constitutive equation of the K-BKZ type has been used for simulating the extrusion of a Low-Density Polyethylene melt (IUPAC LDPE sample A). The influence of temperature has also been examined by performing a complete non-isothermal flow simulation. In addition, simulations have been performed for the well-known phenomenon of extrudate bending, when extrusion is performed through a flat die with walls kept at different temperatures. The simulations reveal that the combination of viscous and elastic phenomena result in a significant swelling of the extrudate characterized by a profound asymmetry. Finally, a comparison has been performed of different polyethylene melts based on the predictions of the model used. The results reveal the intense viscoelastic character of the LDPE and show clearly the importance of viscoelasticity in polymer processing. Moreover, they give a wealth of information about the influence of material properties on polymer behaviour during processing especially as far as vortex growth and extrudate swell diameter are concerned. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.